Anti-EGFR-coated gold nanoparticles in vitro carry 5-fluorouracil to colorectal cancer cells - Liszbinski, Raquel B. [UNESP] (2020)
The aim of the current study is to present a strategy to improve the effciency of 5-fluorouracil (5-FU), which is widely used as antineoplastic agent against solid tumors-based on the use of gold nanocarriers to overcome the resistance of colorectal cancer cells. 5-FU was loaded on gold nanoparticles (AuNP) coated with anti-EGFR antibodies in order to target them towards colorectal cancer cells that overexpress epidermal growth factor receptors (EGFR). Physicochemical characterization has shown that AuNP size was approximately 20 nm and that AuNP functionalization led to spherical nanoparticles. Flow cytometry allowed observing that some compounds synthesized by our research group have induced apoptosis/necrosis and impaired the proliferation of colon cancer cell lines 'HCT-1160 and 'HT-290. The antibody/drug combination in AuNP (AuNP 5FU EGFR) has improved the apoptosis rate and impaired cell proliferation in both cell lines, regardless of the exposure time. Overall, these results have shown that AuNP functionalization with monoclonal antibodies focused on delivering 5-FU to tumor cells is an exciting strategy against colorectal cancer.